The Meaning of Beauty through A Woman Image in Stephenie Meyer's Twilight (NOBEL: Journal of Literature and Language Teaching, 2016)
The presence of women has been questioned by men since ancient time up to now. They tried to define what kind of creature women are. Aristoteles had given the idea of woman that she is male in form but female in virtue. Thomas Aquinas also defined that woman is an imperfect man. In spite of their confusion about women, they like women's presence since they give beauty in life. The beauty of women is not only in men's mind but it also appears through their performance. They look so beautiful so that men want to make them as their partners in life. The meaning of beauty on women has been changed from time to time. In postmodern era, the meaning of beautiful women is not the same with that in the previous era. The elegant performance does not become the measurement anymore. The idea of what 'she becomes' is the indication of beauty itself and it is discussed in the last part of the article.